PERANAN BAHAN HIJAUAN TANAMAN DALAM PENINGKATAN BAHAN ORGANIK DAN STABILITAS AGGREGAT TANAH ULTISOL LIMAU MANIS YANG DITANAMI JAGUNG (Zea mays L.) - Yulnafatmawita Yulnafatmawita; Amrizal Saidi; Gusnidar Gusnidar; Adrinal Adrinal; Suyoko Suyoko (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
A research aiming to improve soil aggregate stability of Ultisol in terms of creating sustainable agriculture and environmental development was conducted by applying fresh organic matter (OM) into soil. Three types of OM sources used were Titonia diversifolia, Chromolaena odorata, dan Gliricidia sepium. This research was conducted in Ultisol Limau Manis Sumbar having annual rainfall > 5000 mm, in 2008. The fresh OM used was cut, mixed with soil up to 20 cm depth, and then incubated for approximately one month before corn seeds were planted. Soil was sampled before being treated with OM and then after harvesting corn (4 moths after applying OM). Soil OM content as well as soil aggregate stability (AS) and several other soil physical properties wer analysed in laboratory. The results showed that soil OM content and AS increased after one planting period. Besides that, soil physical properties were also improved. As soil physical properties became better, corn production was also higher at plot with than without OM application. Among 3 species of OM added, Tithonia diversifolia gave highest corn biomass. Level of land slope (0-8% dan 15-30%) did not show significant difference either for biomass or for soil OM content and soil AS.Key Words: marginal soil, green manure, soil aggregate stability, soil organic matter